CTT in the digitalization era - Cabanas, Sofia Borralho de Vasconcelos (2020)
The world is in constant change and the rapid evolution of technology, among other factors, plays an important role. Thus, it is crucial for organizations to adapt and to implement organizational changes and strategic decisions in order to survive in highly dynamic environments. To better illustrate the theoretical views with a real-life example, I selected the centenary Portuguese postal operator named CTT and how it has responded to the heavy decline of the Mail business. The case study intends to demonstrate the importance of identifying exogenous shocks in the operating market and the associated challenges that can arise to companies. Furthermore, it enhances how poor organizational performance can be a main driver for change. As a response to the shifts in the industry, CTT had a late implementation of a diversification strategy, mainly focused on two growth levers – Banking and Parcels sectors. Nonetheless, the case study shows how CTT’s diversification attempts have affected its core business and its competitive advantage. Moreover, it illustrates the importance of accessing Dynamic Capabilities in order to respond to dynamic environments.